2001
DOI: 10.1046/j.1365-2818.2001.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and quantitative assessment of homogeneous and inhomogeneous particle distributions in particulate metal matrix composites

Abstract: SummaryReinforcement distributions play an important role in various aspects of the processing and final mechanical behaviour of particulate metal matrix composites (PMMCs). Methods for quantifying spatial distribution in such materials are, however, poorly developed, particularly in relation to the range of particle size, shape and orientation that may be present in any one system. The present work investigates via computer simulations the influences of particle morphology, homogeneity and inhomogeneity on sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 18 publications
0
58
0
6
Order By: Relevance
“…It has been found previously that such interface-based finite-body tessellation provides a valuable method of assessing particle distributions in common particulate MMC microstructures, offering significant advantages over Dirichlet tessellation and nearest-neighbor methods. [14,15,16] A variety of parameters relating to particle morphology and spatial distribution may then be derived for each individual particle, for instance, "local" area fraction (ratio of particle area and corresponding tessellation cell area), and mean near-neighbor distance (average of the interface-to-interface separations with all particles that share a cell edge around each individual particle of interest). In particular, the coefficient of variation of mean near-neighbor distance (COV(d mean )), defined as the ratio of the standard deviation and the average of mean near-neighbor distances, has been identified in previous work as a particle-morphologyindependent parameter to quantify homogeneity of particle distributions.…”
Section: A Materials and Microstructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found previously that such interface-based finite-body tessellation provides a valuable method of assessing particle distributions in common particulate MMC microstructures, offering significant advantages over Dirichlet tessellation and nearest-neighbor methods. [14,15,16] A variety of parameters relating to particle morphology and spatial distribution may then be derived for each individual particle, for instance, "local" area fraction (ratio of particle area and corresponding tessellation cell area), and mean near-neighbor distance (average of the interface-to-interface separations with all particles that share a cell edge around each individual particle of interest). In particular, the coefficient of variation of mean near-neighbor distance (COV(d mean )), defined as the ratio of the standard deviation and the average of mean near-neighbor distances, has been identified in previous work as a particle-morphologyindependent parameter to quantify homogeneity of particle distributions.…”
Section: A Materials and Microstructuresmentioning
confidence: 99%
“…In particular, the coefficient of variation of mean near-neighbor distance (COV(d mean )), defined as the ratio of the standard deviation and the average of mean near-neighbor distances, has been identified in previous work as a particle-morphologyindependent parameter to quantify homogeneity of particle distributions. [15,16] It has been shown that a COV(d mean ) value of is indicative of a homogeneous (in this context being taken to mean random) particle distribution. [15,16] Standard image analysis and finite-body tessellation measurements of the present particulate TiB 2 reinforced composite showed that the particles had an average diameter of (as equivalent area circles) and average aspect ratio of 1.4.…”
Section: A Materials and Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The Box-Müller method was also adapted to get a log-normal distribution [32]. Figure 3 gives an example of ellipsoidal generation of inclusions with the localized cluster method [9] and the remeshing method previously described. Some generated REVs were containing more than 300 inclusions gathered in a single cluster.…”
Section: Statistical Generation Of Inclusionsmentioning
confidence: 99%
“…It is given by the inner envelope of the perpendicular bisectors of the lines joining the given point to the other points. Based on the tessellated cell structure, a variety of parameters relating to spatial distribution may be derived, including "neighboring particle" parameters (defined as cells sharing cell boundaries) and near-neighbor distance (defined as the shortest distance between corresponding particle centroids) [19] . For example, Lloyd [65] studied the particle distribution in two particle reinforce MMCs.…”
Section: Particle Distributionmentioning
confidence: 99%